Inovasi Kue Nastar Dengan Substitusi Tepung Singkong (Manihot Esculenta) Dan Penambahan Bubuk Daun Kelor (Moringa Oleifera) - Cantika Shinta Ardiningtyas; Ita Fatkhur Romadhoni; Ila Huda Puspita Dewi; Any Sutiadiningsih (Journal of Creative Student Research, 2023)
This research is about nastar cakes which have the main raw material as wheat flour substituted with cassava flour to reduce the use of wheat flour and the addition of Moringa leaf powder to increase the nutritional content. The purpose of this study is determine 1) the sensory quality of nastar cake with cassava flour substitution and the addition of Moringa leaf powder 2) nutritional and non-nutritional content based on laboratory tests including protein, carbohydrates, fat, water, ash, vitamin C and antioxidants 3) material costs pineapple cake. This type of research is an experiment. Observation data collection techniques by means of sensory quality tests were carried out by 30 panelists. The independent variables of the research were cassava flour substitution (75% and 100%) and the addition of Moringa leaf powder (3g, 5g and 7g). The dependent variable of the research is sensory quality including shape, color, texture, aroma, and taste. The control variables in this study include the types of materials, equipment and processing techniques. Data analysis used two way anova and Duncan. The results showed 1) there was an effect on the sensory quality of making nastar cakes with substitution of cassava flour and the addition of Moringa leaf powder including color, texture, aroma and taste. 2) there is no effect on the sensory quality of the nastar cake shape because it is influenced by the mold. 3) product that are said to be good may contain nutrition equal to or greater according to SNI 2011 including ash content 1.12%, moisture content 4.93%, protein 6.08%, fat 3.81%, carbohydrates 53.10%, vitamin C 16.55 mg/100g and antioxidants 123.60 mg/100g. 4) the best product has a material cost price of IDR 32,806.